A comparative study of the laboratory features of COVID‐19 and other viral pneumonias in the recovery stage. Issue 10 (21st July 2020) - Zhao, Guolian; Su, Yingying; Sun, Xiaomeng; Cui, Xiaoli; Dang, Liyun; Zhao, Lijuan; Tan, Xiaowen; Wang, Hongrui; Yang, Ming
Abstract: Background: Clinical recovery does not mean full recovery. It is necessary to explore the aftereffects of COVID‐19 in patients and compare the laboratory features of COVID‐19 and other viral pneumonias in the recovery stages. Methods: Forty‐seven cases of COVID‐19 and 45 cases of other viral pneumonias (control) were included in this study. The laboratory parameters were compared between COVID‐19 and control patients as well as severe and moderate COVID‐19 patients from the clinical recovery stage to the 4 weeks postdischarge recovery stage. Results: A higher RDW‐CV level and neutrophil percentage and lower levels of total proteins, lymphocytes, eosinophils, and MCH were found in COVID‐19 patients compared with those in controls from the clinical recovery to the postdischarge recovery stages. Further analysis showed that decreases in lymphocytes, total proteins, and SOD and elevations in neutrophils, FDP, CRP, and ESR were more common in severe than moderate cases of COVID‐19 during hospitalization; however, differences in these indicators, except total proteins, were not observed in the postdischarge recovery stages. Additionally, only 76.9% of COVID‐19 patients were positive for IgG antibodies against SARS‐CoV‐2 in the convalescence stage, and one patient that was negative for specific IgG was reinfected. Conclusions: This study demonstrated that patients recovering from COVID‐19 might need better care than that patients with other viral pneumonias due to the possibility of having poor immunity and nutritional conditions. These findings provide new insights to improve the understanding of COVID‐19 and improve care for patients affected by these kinds of pandemics in the future. Abstract : A higher neutrophil percentage and lower levels of total proteins and lymphocytes were found in COVID‐19 patients compared with those in other viral pneumonia patients from the clinical recovery to the postdischarge recovery stages. This study demonstrated that patients recovering from COVID‐19 might need better care than that patients with other viral pneumonias due to the possibility of having poor immunity and nutritional conditions.